The Antihistamine Drugs Carbinoxamine Maleate and Chlorpheniramine Maleate Exhibit Potent Antiviral Activity Against a Broad Spectrum of Influenza Viruses - Xu, Wei; Xia, Shuai; Pu, Jing; Wang, Qian; Li, Peiyu; Lu, Lu; Jiang, Shibo (Frontiers in Microbiology, 2018)
Influenza A viruses (IAV) comprise some of the most common infectious pathogens in humans, and they cause significant mortality and morbidity in immunocompromised people as well as children and the elderly. After screening an FDA-approved drug library containing 1280 compounds by cytopathic effect (CPE) reduction assay using the Cell Counting Kit-8, we found two antihistamines, carbinoxamine maleate (CAM) and S-(+)-chlorpheniramine maleate (SCM) with potent antiviral activity against A/Shanghai/4664T/2013(H7N9) infection with IC50 (half-maximal inhibitory concentration) of 3.56 and 11.84 μM, respectively. Further studies showed that CAM and SCM could also inhibit infection by other influenza A viruses, including A/Shanghai/37T/2009(H1N1), A/Puerto Rico/8/1934(H1N1), A/Guizhou/54/1989(H3N2), and one influenza B virus, B/Shanghai/2017(BY). Mice were challenged intranasally with A/H7N9/4664T/2013 (H7N9) virus and intraperitoneally injected with CAM (10 mg/kg per day) or SCM (1 mg/kg per day) for 5 days. CAM or SCM (10 mg/kg per day) were fully protected against challenge with A/Shanghai/4664T/2013(H7N9). The results from mechanistic studies indicate that both could inhibit influenza virus infection by blocking viral entry into the target cell, the early stage of virus life cycle. However, CAM and SCM neither blocked virus attachment, characteristic of HA activity, nor virus release, characteristic of NA activity. Such data suggest that these two compounds may interfere with the endocytosis process. Thus, we have identified two FDA-approved antihistamine drugs, CAM and SCM, which can be repurposed for inhibiting infection by divergent influenza A strains and one influenza B strain with potential to be used for treatment and prevention of influenza virus infection.